A Note on Optimal Tax Depreciation Research. - Stickney, Clyde P. (The Accounting Review, 1981)
ABSTRACT: This paper critically examines the development and current status of research on optimal tax depreciation decisions. It is shown that various researchers have derived piecemeal solutions to an existing decision model and have failed to reflect correctly important provisions of the income tax law. Questions are raised regarding the relative contribution of such studies to the stock of knowledge and the criteria for evaluating future research on optimal tax choices.